Pengaruh Kepemimpinan, Motivasi dan Lingkungan Kerja Terhadap Kinerja Tenaga Pendidik dan Kependidikan pada STIE Kalpataru Bogor - Bukhari Muslim (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
The aim of this research is to determine the influence of Leadership, Motivation and Work Environment on the Performance of Educators and Education Personnel at STIE KALPATARU. The population in this study consisted of all educators and educational staff with a sample size of 68 people at STIE-Kalpataru. The data collection technique was a questionnaire that was distributed and then tested for validity and reliability. The data analysis techniques used are correlation analysis, regression analysis, coefficient of determination, t test and f test. The research results obtained are: 1). Leadership (X1) on the performance of educators and educational staff (Y) is a multiple linear regression analysis. The results of the research show that the influence of leadership, motivation and work environment on the performance of teaching and education staff has a significant influence both physically simultaneous or partial towards STIE KALPATARU.